THE QUEST FOR HOME IN AMITAV GHOSH’S THE SHADOW LINES, THE GLASS PALACE, AND THE HUNGRY TIDE - Singh, Vikram; Deep, Aman; Ritu; Manisha (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The present paper sheds light on the intricate themes of home, identity, and displacement in Amitav Ghosh’s The Shadow Lines, The Glass Palace, and The Hungry Tide. Ghosh intertwines personal narratives with larger historical contexts, analyzing the impact of events such as the Partition, colonialism, and postcolonial transitions on the individual and collective psyche. His narratives challenge conventional notions of belonging and borders, employing vivid metaphors, allegories, and intergenerational stories to reveal the complexities of identity formation. He portrays the fluidity of identity and the dissonance between emotional and geographical conceptions of home, illustrating how displacement, exile, and migration alter the human experience. Through characters grappling with exile, memory, shifting boundaries, identity crises, and the loss of homeland, the paper highlights the universal human quest for belonging amidst political upheavals, cultural dislocations, and social transformations. By exploring the intersections of nationalism, diaspora, and memory, Ghosh critiques artificial divisions and dismantles myths of fixed identities. His works transcend individual stories to underscore displaced communities’ resilience, adaptability, and agency. His oeuvre invites a rethinking of concepts like home, identity, and belonging in an ever-changing historical and cultural landscape by presenting a poignant reflection on the enduring struggle to reconcile fragmented identities within a globalized and divided world.